Towards a Time-Aware Hidden Markov Model for the Truco Game - Assunção, Joaquim; Paulus, Gustavo Bathu (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais Estendidos do XXI Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2022.225638, 2022)
Similar to Poker, the game of Truco has challenges for Artificial intelligence. Considering a large number of game states, a scenario characterized by partial visibility, stochastic behavior, and score susceptible to bluff; this game offers a good set of rules to test and improve AI techniques. In this article, we describe the creation of a Hidden Markov Model (HMM) agent using temporal control. The model has an embedded vector that adjusts its probabilities for further game actions, consequently, improving the model playing performance. The evaluation is given with over 210,000 matches, serving as empirical proof of the idea.